Impact of social and clinical factors on diagnostic delay of breast cancer: A Cross-sectional Study. Issue 38 (September 2016) - Dianatinasab, Mostafa; Fararouei, Mohammad; Mohammadianpanah, Mohammad; Zare-Bandamiri, Mohammad
Abstract : Abstract: One of the reasons for high mortality of breast cancer is long delay in seeking medical care. This study was designed to measure the association of a wide range of socio-demographic and clinical factors with the diagnostic delay in breast cancer among Iranian patients. This study was conducted on 505 newly diagnosed patients with breast cancer from southern part of Iran. Medical files of the patients who were admitted to the hospital from November 2013 to May 2015 were examined and clinical and demographic information were extracted. According to the results, illiterate patients were diagnosed on average 87.42 days later compared with those with a college degree (95%CI: 29.68–145.16, P = 0.003) and those from rural area were diagnosed on average 72.48 days later (95%CI: 35.94–109.03, P = 0.001) compared with urban residences. Single women were diagnosed 65.99 days later (95%CI: 7.37–124.61, P = 0.02) compared with those married. Lobular or medullary types of cancer were diagnosed 65.19 days later (95%CI: 2.67–127.70, P = 0.04) compared with ductal type. On the other hand, those who were able to perform breast self-exam were diagnosed 49.07 days earlier compared with others (95%CI: 18.69–79.45, P = 0.002). Those felt lump as the initiating symptom were diagnosed 62.01 days earlier, (95%CI: 8.17–115.85, P = 0.02) compared with those with other initial symptoms. The only factor associated with doctors diagnosis delay was the place of residence as rural residences were diagnosed on average 87.42 days later compared with urban residences, (95%CI: 53.82–121.92, P = 0.001). Higher education, living in cities, ductal type of tumor, and noticing lump in breast were the most important demographic and clinical factors associated with shorter breast cancer diagnosis delay. Informing women and doctors, especially general physicians who are practicing in rural areas, of the common symptoms of breast cancer as well as training women to perform breast self-examination are effective measures in reducing breast cancer diagnosis delay. Providing accessible and effective diagnosis services to rural women reduces diagnosis delay in rural patients.